Genotypic interrelationships for flowering traits in sugarcane genotypes treated by Gibberellic acid under natural conditions - Farrag F. B. Abu-Ellail; E.S.R. Salem; El-Sheikh A.M. (Journal of Sugarcane Research)
The low ﬂowering intensity of some sugarcane germplasm decreases seed yield. Flowering ability and intensity are desired traits for a successful sugarcane breeding program. The goal of the study  was to evaluate the eﬀects of  various foliar gibberellic acid (GA3) concentrations (0, 50, and 100 mg l⁻¹) on 20 sugarcane  genotypes to improve their ﬂowering ability and intensity under natural conditions at El-Sabahia Research Station (31o  12 54″ N and 29o  58' 23″ E),  Alexandria, Egypt, over the plant and ratoon cane crops grown in the 2020/2021 and 2021/2022 seasons. The results revealed that increasing GA3 concentrations up to 100 mg/l improved the ﬂowering percentage during the various ﬂowering stages of the 20 sugarcane genotypes. Sugarcane genotypes, namely MEX2001-80, Co1129, and CP63-49, outperformed the others during the ﬂowering stages. The interactions between sugarcane genotypes and GA3  concentrations had a signiﬁcant impact on ﬂowering percentage. According to cluster analysis, the longest full emergence ﬂowering period was 142.24 days, whereas the shortest period was 0.0 days. It was discovered that the Mex 2001–80 genotype's superiority in longevity was mostly due to its superiority in the emergence stage. The GT biplot's polygon view was used to identify the genotypes that showed good ﬂowering responses for one or more GA3  concentrations. According to the study, the responsive sugarcane genotypes may be treated with 100 mg/l of GA3 to induce ﬂoral primordia, which will speed up and intensify ﬂowering. Selection should concentrate on tip emergence stage and full emergence stage to increase ﬂowering percentage, according to genotypic correlation.  Finding the best sugarcane genotypes in natural settings is crucial, as evidenced by the necessity for additional research using higher concentrations of GA  to evaluate all sugarcane germplasms for ﬂowering ability and intensity.